The role of the Field Epidemiology Training Program in the public health emergency response: Sudan armed conflict 2023 - Khairy, Amna; Bashier, Haitham; Nuh, Hatim; Ahmed, Nagla; Ali, Yousif; Izzoddeen, Ahmad; Mohamed, Sara; Osman, Muntasir; Khader, Yousef (Frontiers in Public Health, 2024)
Background: On April 15, 2023, the armed conflict between the Sudanese Armed Forces (SAF) and the Rapid Support Forces (RSF) started in Khartoum state, Sudan. This conflict was complicated by the preexisting complicated epidemiological situation and fragile health system in Sudan. This study endeavors to illuminate the pivotal role essayed by the Sudan FETP (SFETP) in enhancing the nation's public health response, particularly amidst the tumultuous backdrop of armed conflicts that have left their indelible mark on the region. Methods: Employing a blend of quantitative and qualitative methodologies, we investigated the SFETP's contributions to the public health response during the initial four months of the conflict (April-July 2023). Sixty-four SFETP residents and graduates were invited to participate, and data were gathered through semi-structured questionnaires. Results: A total of 44 (69%) SFETP residents and graduates were included in this study. Out of 38 SFETPs present in the states, 32 have considerably contributed to the crisis response at state and locality levels. Three-quarters of them have played key leadership, planning, and management roles. In essence, 38% (n=12) of them have contributed to public health surveillance, particularly in data management, reports, Early Warning Alert and Response System (EWAR) establishment, and epidemic investigation. SFETPs have made special contributions to crisis response at the community level. The involved SFETPs supported WASH interventions (n=4), and almost one-third of them strengthened risk communication and community engagement (n=9). Despite their physical presence at the subnational level, 27% of graduates were not deployed to the crisis emergency response. Notably, throughout this time, half of the total SFETPs were formally retained during this response. Conclusion: The study highlighted the importance of FETP engagement and support during public health crises. SFETP residents and graduates played diverse roles in the various levels of public health emergency response to the crisis. However. Strategies to improve the deployment and retention of FETP residents are necessary to ensure their availability during crises. Overall, FETP has proven to be an asset in public health crisis management in Sudan. Keywords. Armed Conflict, Field Epidemiology, Crisis Response